2014
DOI: 10.1155/2014/925981
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Recreational Exercise in TNBS-Induced Colitis in Rats: Role of NOS/HO/MPO System

Abstract: There are opposite views in the available literature: Whether physical exercise has a protective effect or not on the onset of inflammatory bowel disease (IBD). Therefore, we investigated the effects of recreational physical exercise before the induction of colitis. After 6 weeks of voluntary physical activity (running wheel), male Wistar rats were treated with TNBS (10 mg). 72 hrs after trinitrobenzene sulphonic acid (TNBS) challenge we measured colonic gene (TNF-α, IL-1β, CXCL1 and IL-10) and protein (TNF-α)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 41 publications
5
39
3
3
Order By: Relevance
“…However, a previous study showed that TNBS-induced mice had decreased inflammatory cytokine expression (IL-1β and TNF-α) after 6 weeks of wheel running. 3 Although the results of this previous study suggest that physical activity has a positive effect on IBD, high-intensity exercise can induce a genetic environment similar to IBD, as suggested in the present study.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…However, a previous study showed that TNBS-induced mice had decreased inflammatory cytokine expression (IL-1β and TNF-α) after 6 weeks of wheel running. 3 Although the results of this previous study suggest that physical activity has a positive effect on IBD, high-intensity exercise can induce a genetic environment similar to IBD, as suggested in the present study.…”
Section: Discussioncontrasting
confidence: 42%
“…1,2 Exercise induces inflammatory cytokines IL-1β and TNF-α, stimulating T and B cell production through inflammation induction and immune control action. 3 Thus, high-intensity exercise can be a cause of diseases related to abnormalities in the immune system via the induction of inflammatory cytokines. 4 Furthermore, high-intensity exercise causes inflammation through ischemia to the organs.…”
Section: E23mentioning
confidence: 99%
“…Hoffman-Goetz et al [28] carried out a controlled study in mice; 3 bouts of sustained and vigorous treadmill running increased levels of the anti-inflammatory cytokine IL-10 and decreased levels of TNF-α in intestinal lymphocytes relative to values for control animals. Szalai et al [62] also found evidence of benefit from recreational levels of exercise (wheel-running) in rats with TNBS-induced colitis in terms of decreased pro-inflammatory genes, the induction of antiinflammatory mediators, and modulation of the activity of HO and NOS enzymes. A controlled study of rats with an acetic acidinduced colitis confirmed that 6 weeks of moderate exercise on a running wheel (0.4 km/h, for 30 min, 3 days/wk) reduced markers of oxidative stress, and histological damage to the colon, in association with a reduction of stress as assessed by holeboard tests [32].…”
Section: Endocrine and Immune Functionmentioning
confidence: 98%
“…En un estudio de Zsalai (2014) se analizaron los efectos del ejercicio en trastornos gastrointestinales, probando en ratas con colitis ulcerosa, y se pudo ver que el ejercicio juega un rol antiinflamatorio por la desregulación de genes proinflamatorios. 46 Se puede observar que los efectos favorecedores del ejercicio en el endotelio vascular como a nivel sistémico cumplen un rol relevante en la prevención y como estrategia de tratamiento de enfermedades que generan grados de inflamación. La TVP aguda y consecuentemente el síndrome postrombótico generan estados inflamatorios que pueden ser aliviados por la correcta prescripción y dosificación del entrenamiento físico.…”
Section: Ejercicio Y Función Vascularunclassified